2020
DOI: 10.3390/s20030830
|View full text |Cite
|
Sign up to set email alerts
|

In-Vivo and Ex-Vivo Measurements of Blood Glucose Using Whispering Gallery Modes

Abstract: The permittivity of blood glucose is not a strong function of its concentration in microwave or millimeter-wave frequencies. Measuring glucose concentrations remains a challenge, particularly in the presence of interference caused by the ambient leaky waves. In this paper, however, we demonstrate that a near-linear correlation between the glucose concentration and the blood permittivity was noticeably observed at a whispering gallery mode resonance. Method: the proposed sensor was a vacuum suction aspirator pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Nevertheless, the spoof-plasmon-based transmission lines usually exhibit higher attenuation than Goubau lines [ 14 ] and the latter is currently in the further development stage. A number of electronic devices have been proposed based on the concept of the Goubau line, to name a few, wideband transmission lines [ 4 , 15 ] and passive components [ 16 ], leaky-wave antennas [ 14 , 17 , 18 ], frequency-selective configurations [ 11 , 12 , 19 ], sensors [ [20] , [21] , [22] ], etc. In particular, Parker-Jervis et al designed a tunable bandstop filter in the THz spectrum using two coupled split-ring resonators integrated with a planar Goubau line and achieved a relatively high Q-factor around 60 at about 270 THz [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the spoof-plasmon-based transmission lines usually exhibit higher attenuation than Goubau lines [ 14 ] and the latter is currently in the further development stage. A number of electronic devices have been proposed based on the concept of the Goubau line, to name a few, wideband transmission lines [ 4 , 15 ] and passive components [ 16 ], leaky-wave antennas [ 14 , 17 , 18 ], frequency-selective configurations [ 11 , 12 , 19 ], sensors [ [20] , [21] , [22] ], etc. In particular, Parker-Jervis et al designed a tunable bandstop filter in the THz spectrum using two coupled split-ring resonators integrated with a planar Goubau line and achieved a relatively high Q-factor around 60 at about 270 THz [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive measurements can be made with microneedle patches or implantable sensors , consisting of glucose-responsive materials such as glucose oxidase ,, or phenylboronic acid gel. Although securing enough glucose selectivity is a challenging issue, noninvasive measurements using electromagnetic waves, ultrasonic waves, and magnetic resonance have great potential to liberate patients of the above-mentioned burden. In particular, gigahertz-band electromagnetic waves (microwaves) that penetrate the skin can be used to measure glucose in aqueous solutions, saline solutions, and hydrogels, as well as in animals and humans. , In addition, there are various means of radiating radio waves, for example, open-ended coaxial probes, split-ring resonators, , microstripe antennas, patch antennas, cavity sensors, coplanar sensors, and multimodality analysis . Biomimetic homogeneous hydrogel phantoms made of, for instance, gelatin, agarose, poly­(methyl methacrylate), and flour can be used in combination with computer simulations , for validation before the experiments are conducted on actual organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, gigahertz-band electromagnetic waves (microwaves) that penetrate the skin can be used to measure glucose in aqueous solutions, 23−26 saline solutions, 27−29 and hydrogels, 30−32 as well as in animals 11 and humans. 33,34 In addition, there are various means of radiating radio waves, for example, openended coaxial probes, 35 split-ring resonators, 36,37 microstripe antennas, 38 patch antennas, 39 cavity sensors, 40 coplanar sensors, 41 and multimodality analysis. 42 Biomimetic homogeneous hydrogel phantoms 43−46 made of, for instance, gelatin, 43 agarose, 44 poly(methyl methacrylate), 45 and flour 46 can be used in combination with computer simulations 47,48 for validation before the experiments are conducted on actual organisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, researchers are using microwave sensing technology for blood glucose detection at the clinical level. Liu et al [ 25 ] proposed a microwave resonator-based glucose sensor based on the whispering gallery mode resonance technique for in vivo detection. The authors observed that the in vivo measurement was correlated with the ex vivo measurement (glucose/water solution).…”
Section: Introductionmentioning
confidence: 99%